A Influência Dos Estilos De Liderança Na Capacidade De Aprendizagem No Uso Do Orçamento: Um Estudo Em Cooperativas Agroindustriais - Silva, Elvis Joel Rodrigues da (2022)
This research investigated the influences of leadership styles on learning capacity and the types of use of the corporate budget in agro-industrial cooperatives. This is descriptive research, as to the objectives, of the field survey, as to the procedures, and quantitative, as to the approach, since statistical techniques and resources were used for the analysis. The data, in turn, were collected employing questionnaires, answered electronically by 89 middle managers. It was possible to verify that the leadership styles - transformational or transactional - influence the learning capacity within the cooperatives and the use of the budget. Another relevant consideration was that the transformational style did not show influence in the interactive use of the budget, contrary to other studies in the area, a fact that may be related to the branch of activity of the researched organizations or even to the culture of the cooperatives. In theoretical terms, it is considered that the proposal advanced by bringing evidence that the leadership style can influence certain aspects of the budget and the learning capacity within the cooperatives. Moreover, this research contributed to the literature by relating the leadership style to the learning capacity and the use of the budget, in which the learning capacity results from how the actions of the leader can mediate and provide an intellectual evolution to the employees. In practical terms, it is suggested that managers motivate employees to develop intellectually.